Commercial Intratheater Airlift Cost-Effectiveness Analysis of Use in U.S. Central Command - McGarvey, Ronald G. (RAND Corporation, 2013)
Intratheater airlift delivers critical and time-sensitive supplies to deployed forces. Traditionally, military aircraft have provided this airlift. However, in recent years, commercial carriers provided a significant amount of airlift within U.S. Central Command. The authors examine whether the use of commercial airlift was more cost-effective than using organic U.S. Air Force aircraft for these historical movements.